Book Review: Representation of the Past in Public Spheres. Experiencing the Past: the Reconstruction and Recreation of History at Colonial Williamsburg by Martine Teunissen - Evelyn Fidler (EXARC Journal)
When I read the title, I particularly looked forward to reading this book and I was not disappointed. I am glad I was allowed to review it. Colonial Williamsburg has been held up to me as an example to follow when interpreting in living history and open air museums and also criticised when they don’t get it right. I was curious to see why and how they reached that reputation.